A NARRATIVE ANALYSIS OF IDENTITY CONSTRUCTION IN ONLINE PLATFORM LITERATURE - Nensilianti, Nensilianti; Ridwan, Ridwan; Tuflih, Muhammad Alfian (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study investigates the construction of cultural identity in digital literature through a narrative analysis of works published on Wattpad, Webtoon, and literary blogs. It responds to the paradigm shift in communication and cultural expression driven by rapid digital technological advances, which position digital literature as an interactive space between authors and readers. The study aims to identify mechanisms of cultural identity formation through narrative elements and to examine the influence of user interaction in shaping these processes. Employing a qualitative design, it integrates narrative analysis, critical discourse analysis, and hermeneutic interpretation. Data were collected via purposive sampling of 30 representative digital literary works, documentation of reader–author interactions, and in-depth interviews. Findings reveal three dominant strategies: integrating local symbols and values, depicting characters as embodiments of collective identity, and adapting traditions into visual–interactive formats. Interaction analysis shows that 78% of reader comments reinforce or reinterpret cultural identity, while 65% of authors acknowledge the influence of reader feedback. The study’s novelty lies in proposing an interdisciplinary narrative analysis framework synthesising literary theory, digital culture, and participatory communication, thereby advancing digital literature scholarship and offering strategic recommendations for platforms and authors to optimise digital media in constructing cultural identity.